Gastric Cancer: A Comprehensive Review of Current and Future Treatment Strategies - Sexton, Rachel E. (Cancer Metastasis Rev, 2020)
Gastric cancer remains a major unmet clinical problem with over 1 million new cases in 2018 worldwide. It is the fourth most commonly occurring cancer in men and the seventh most commonly occurring cancer in women. A major fraction of gastric cancer has been linked to variety of pathogenic infections including but not limited to Helicobacter pylori (H. pylori) or Epstein Barr virus (EBV). Strategies are being pursued to prevent gastric cancer development such as H. pylori eradication, which has helped to prevent significant proportion of gastric cancer. Today, treatments have helped to manage this disease and the 5-year survival for stage IA and IB tumors treated with surgery are between 60% and 80%. However, patients with stage III tumors undergoing surgery have a dismal 5-year survival rate between 18% and 50% depending on the dataset. These figures indicate the need for more effective molecularly driven treatment strategies. This review discusses the molecular profile of gastric tumors, the success and challenges with available therapeutic targets along with newer biomarkers and emerging targets.